Introduction to the Special Issue on Physician Mental Health - Pamela Wible (Qualitative Research in Medicine & Healthcare)
Amid tragedy, a doctor’s most heroic act may be to listen - to be a sacred witness to the suffering of patients. Yet where do heroic doctors go with their pain? Who listens to the suffering of physicians? The guilt of not being able to do more for patients. The burden of delivering devastating news to families. The work-related anxiety and depression due to unrealistic expectations of perfectionism. (...)